Analysis of the Contribution of Major Economic Sectors to Employment Improvement in Balikpapan - Nur Aini Agustina; Riko Setya Wijaya (International Journal of Economics, Business and Innovation Research, 2024)
The existence of a just society, which includes justice and equity across the region, is a challenge to future progress. This can be achieved through increasing sectoral development that focuses on building growth centers that can increase economic growth. Prioritizing regions in accordance with the economic potential and superior industries is the main policy. In addition, the focus of the development program is to create new jobs, both in the agricultural and non-agricultural sectors. In this study, the aim is to find out the superior and superior sectors, analyze economic shifts, and the difference in the influence of superior and non-superior sectors on labor absorption. The location of this research is in the Balikpapan area using secondary data in the form of a time series in the 2013-2022 time frame. This study uses a quantitative approach with LQ analysis methods, regional Klassen typology, and simple regression. The results of the study show that based on the results of the Location Quotient (LQ) analysis of Balikpapan City shows that there are 6 leading sectors, the results of the Balikpapan City Klasen Typology analysis show that Balikpapan City is included in the Quadrant 2 classification with the category of Fast Developing Regions. Based on the results of a simple linear regression analysis test, there is a difference in the influence of superior sectors and non-superior sectors in absorbing labor, Significantly superior sectors are able to influence in absorbing labor. Meanwhile, the non-superior sector is significantly unable to influence in absorbing labor in Balikpapan City.